ANALISIS TECHNOLOGICAL PEDAGOGICAL CONTENT KNOWLEDGE (TPACK) CALON GURU BIOLOGI UNIVERSITAS AHMAD DAHLAN - Handayani, Trikinasih; Aprilia, Nani; Susanti, Ani; Alpendi, Alpendi (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
Global challenges demand the availability of human resources (HR) who master science, technology, and art (IPTEKS). The acceleration of educational change is oriented towards the use of technology, especially the integration of learning. Related to these changes, professional teachers are required to have competency in line with existing developments with TPACK (Technological Pedagogical Content Knowledge) skills for the realization of quality education. This study aims to analyze the TPACK ability of prospective biology teachers. The research was conducted using a survey method in the form of self-report-measure. The research sample was 150 biology students in semesters 7 and 8 using a random sampling technique. Data collection was carried out using a questionnaire. The questionnaire was developed from the TPACK questionnaire created by Schmidt et al (2009) and Sahin (2001). The instrument has been tested for validity with a p-value < 0.05 and the reliability of Cronbach's Alpha > 0.05. 0.70. After the data was analyzed, the TPACK abilities of prospective biology teachers were grouped into 5 levels, namely very good, good, medium, and low. The results showed that the preservice teachers in Biology education Universitas Ahmad Dahlan Technological Pedagogical Content Knowledge (TPACK) skills obtained an average of 3.51-4.50 including having good TPACK abilities. Kata kunci: Analysis; Technological Pedagogical and Content Knowledge (TPACK); calon guru